Laporan Kasus: Seorang Laki-Laki Usia 48 Tahun dengan Herniasi Nukleus Pulposus Servikal - Muhammad Alka Fakhrizal; Muhammad Ricky Ramadhian; Danang Samudro Wicaksono; Frecilia Afrida; Yovani Tria Ananda (Medula, 2026)
Cervical herniated nucleus pulposus is a common cause of neck pain, radicular pain, and neurological deficits resulting from compression of cervical nerve roots by intervertebral disc pathology. The incidence of cervical radiculopathy peaks in the fourth and fifth decades of life and is closely associated with degenerative disc changes. This report presents the case of a 48 year old male who complained of chronic neck pain radiating to the upper back and right upper extremity, accompanied by paresthesia, restricted cervical range of motion, and weakness during right arm elevation. The symptoms had persisted for one year and progressively worsened over the last two months, with no history of trauma. The patient also reported intermittent burning sensations that improved with rest. These clinical features were consistent with cervical radiculopathy caused by progressive cervical disc herniation. Magnetic resonance imaging of the cervical spine in sagittal sections revealed disc protrusion at the C5 C6 level causing anterior spinal canal compression, as well as mild disc protrusion at C6 C7 with narrowing of the anterior subarachnoid space. Thoracic spine MRI showed no significant abnormalities. Initial management consisted of conservative therapy using non steroidal anti inflammatory drugs and gabapentin to address inflammatory and neuropathic pain components. Due to persistent symptoms and motor weakness, surgical intervention with percutaneous endoscopic cervical discectomy was planned. A thorough understanding of cervical spine anatomy, disc herniation pathophysiology, clinical manifestations, and imaging findings is essential for accurate diagnosis and appropriate treatment selection to prevent symptom progression and deterioration of patient quality of life.